Relay Catalysis by a Ruthenium Complex–Chiral Brønsted Acid Binary Sytem for Ternary Reaction Sequence Involving Enantioselective Pictet–Spengler-Type Cyclization as the Key Step - Toda, Yasunori; Terada, Masahiro (Synlett, 2013)
Relay catalysis for a ternary reaction sequence composed of double-bond isomerization, protonation of the double bond, and enantioselective Pictet–Spengler-type cyclization was accomplished using a binary catalytic system consisting of a ruthenium hydride complex and a chiral phosphoric acid as the chiral Brønsted acid catalyst.
Keywords: asymmetric catalysis; isomerization; protonation; cyclization; phenols